Protecting the children’s right to nationality in Malaysia: An appraisal - Che Soh @ Yusoff, Roslina; Mohd Badrol Afandi, Nor Hafizah; Md Hashim, Noraini; Abdul Hak, Nora (2017)
Article 7 of the Convention on the Rights of the Child 1989 (CRC) obliges states to realise every child‘s right to acquire a nationality. Even though most human rights should be enjoyed by all persons, regardless of whether they have a nationality or not, in our modern world, nationality often operates as a legal or practical gateway to the enjoyment of other rights. Where a child lacks a nationality, this creates a situation of severe disadvantage and vulnerability. Statelessness undermines the enjoyment of childhood and the child‘s opportunity to develop to his or her full potential. Many stateless children are excluded from the benefits of education and are denied equal access to other rights. Such situation is definitely in contravention with the basic principle of best interest of the child as promulgated in Article 3 of the CRC. This paper addresses the extent of the rights of children in Malaysia to acquire nationality particularly in cases involving unregistered birth, illegitimate, foundling or abandoned child and where the immigration status of the parents is uncertain. This paper uses a qualitative data collection method where in-depth document analysis is carried out. Primary sources such as the Acts, Regulations, court orders and decision are scrutinised. On the other hand, secondary sources that are studied include international document reports from relevant websites, law reports, law reviews, legal periodical articles and news paper reports. The paper is significant as it addresses crucial concerns raised in reference to the current laws relating to the protection of these children in Malaysia. The paper ends with some possible recommendations that may spur improvement to the present legislations towards achieving a sustainable future for the best interest of these children.